Preliminary analysis of compression system integrated heat management concepts using LH2-based parametric gas turbine model - Abedi, Hamidreza; Xisto, Carlos M.; Jonsson, Isak; Grönstedt, Tomas; Rolt, Andrew Martin (MDPI, 2022)
The investigation of the various heat management concepts using LH2 requires the development of a modeling environment coupling the cryogenic hydrogen fuel system with turbofan performance. This paper presents a numerical framework to model hydrogen-fueled gas turbine engines with a dedicated heat-management system, complemented by an introductory analysis of the impact of using LH2 to precool and intercool in the compression system. The propulsion installations comprise Brayton cycle-based turbofans and first assessments are made on how to use the hydrogen as a heat sink integrated into the compression system. Conceptual tubular compact heat exchanger designs are explored to either precool or intercool the compression system and preheat the fuel to improve the installed performance of the propulsion cycles. The precooler and the intercooler show up to 0.3% improved specific fuel consumption for heat exchanger effectiveness in the range 0.5–0.6, but higher effectiveness designs incur disproportionately higher pressure losses that cancel-out the benefits.
Keywords: cryogenic fuel; liquid hydrogen; heat exchanger; precooling; intercooling; Thrust Specific Fuel Consumption